Perceptions of resuscitation care among in-hospital cardiac arrest responders: a qualitative analysis - Samyukta Mullangi; Rohan Bhandari; Porama Thanaporn; Mary Christensen; Steven Kronick; Brahmajee K. Nallamothu (BMC, 2020)
Abstract Background In-hospital cardiac arrests (IHCA) occur commonly and are associated with poor survival and variable outcomes. This study aimed to directly survey IHCA responders to understand their perceptions of resuscitation care. Methods As part of a quality improvement initiative, we surveyed participating providers of IHCAs at our institution from Jan 2014 to May 2016. The survey included unstructured free text feedback, which was the focus of this study. We systematically coded the free text and organized identifiable latent themes using thematic analysis. We used the natural timeline of an IHCA - pre-arrest, arrest, and post-arrest - for organization of the identifiable latent themes, and created a separate category for holistic remarks that arched across the timeline. Results We identified 172 IHCAs with a mean of 1.7 responses per arrest (range: 1-8 responses). The mean age of this patient population was 59 years at the time of arrest, and 107 (62%) were men. We identified several themes - [1] issues around code activation and code status characterized the pre-arrest period [2] ,team interactions and issues around supplies/equipment dominated the intra-arrest period, and [3] code cessation and transitions of care typified the post-arrest period. Holistic remarks focused on attentiveness paid by the arrest team to patient comfort and family. Some comments reflected positive experiences but most focused on areas of improvement consistent with the initiative's purpose. In certain cases, we identified a tension between the need to balance established resuscitation protocols with flexibility required by real-life circumstances. Conclusions Directly surveying those who participated in IHCAs led to novel insights about their experiences. Our findings suggest that parsing through such qualitative feedback can help hospitals identify areas of improvement, modulate expectations, temper emotions, and refine protocols.